Analysis of drivers of agricultural growth, feminization of agriculture and crop modeling tools. A capacity building workshop for the taskforce members of RNR Strategy 2040 for Bhutan. - Pathak, Himanshu (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
The Ministry of Agriculture and Forests (MoAF), Royal Government of Bhutan, had formed a taskforce with members from all sub-sectors and agencies under the Ministry to formulate the RNR1 Strategy 2040 by June 2020. The RNR Strategic Document 2040 will serve as an input to the national level strategic document that the Gross National Happiness Commission is currently formulating. However, to undertake this important task of sectoral envisioning, there exists a technical gap in terms of human resource capacity with respect to various economic analysis required to prepare a long-term strategy. To bridge this gap, a customized training on landscape planning, scenario analysis, and envisioning is deemed crucial to enable and enhance the taskforce to develop the Strategic vision for RNR sector. To fill this gap, MoAF and the International Food Policy Research Institute (IFPRI) collaborated to utilize IFPRI’s knowledge services in developing capacity of the taskforce members. The primary aim of the collaboration is to enable the taskforce in doing evidencebased research. IFPRI will play an important role as knowledge partner to MoAF to provide technical support to the taskforce members in analysing data, implement economic modelling tools using national-level data and simulate it with various alternative policy scenarios. In addition, research team from IFPRI is also responsible to critically review the strategic document and to provide necessary feedback to make the document scientific, evidence-based and implementable.